On distortion of quasiregular mappings of the upper half plane - Fujimura, Masayo; Vuorinen, Matti (TAYLOR & FRANCIS LTD, 2025)
We prove a sharp result for the distortion of a hyperbolic-type metric under K-quasiregular mappings of the upper half plane. The proof makes use of a new kind of Bernoulli inequality and the Schwarz lemma for quasiregular mappings.